Improvement of the numerical modelling in orthogonal dry cutting of an AISI1045 steel by the introduction of a new friction model. (14th April 2011) - Bonnet, C.; Rech, J.; Hamdi, H.; D'Eramo, E.
The numerical modelling of cutting processes remains an issue for scientists. A better understanding of friction modelling is required to lead to more realistic finite element models (FEMs). This work proposes to evaluate the performance of a new friction model depending on the local sliding velocity. This model has been applied to the investigation of an AISI1045 steel in dry orthogonal cutting. The friction model has been implemented in a FEM based on the Arbitrary Lagrangian-Eulerian (ALE) approach. A large spectrum of cutting velocities and feed rates has been investigated. In parallel, experimental orthogonal cutting test have been performed in order to evaluate the accuracy of the model for each cutting condition. The model has shown a very good agreement with experimental results.